Volunteering for a Lifetime? Volunteers’ Intention to Stay in Portuguese Hospitals - Ferreira, Marisa R. (2014)
The current study aims to study Hospital volunteers’ intention to stay in an organization through understanding motivation, management factors, and satisfaction. A total of 304 Hospital volunteers, mainly women, completed a questionnaire measuring motivations, management factors, satisfaction, and intention to stay. In this study, structural equation modeling was used. Results demonstrate that there is a positive relationship between (a) motivation and satisfaction, (b) management factors and satisfaction, (c) satisfaction and intention to stay, and (d) motivation and management factors. These results present important outcomes that should be reflected in the way organizations operate. This research indicates aspects which are most valued by volunteers and allows NPOs to design and establish appropriate and assertive management policies.